Full-length recombinant antibodies from Escherichia coli: production, characterization, effector function (Fc) engineering, and clinical evaluation - Md Harunur Rashid (Taylor & Francis Group, 2022)
Although several antibody fragments and antibody fragment-fusion proteins produced in Escherichia coli (E. coli) are approved as therapeutics for various human diseases, a full-length monoclonal or a bispecific antibody produced in E. coli has not yet been approved. The past decade witnessed substantial progress in expression of full-length antibodies in the E. coli cytoplasm and periplasm, as well as in cell-free expression systems. The equivalency of E. coli-produced aglycosylated antibodies and their mammalian cell-produced counterparts, with respect to biochemical and biophysical properties, including antigen binding, in vitro and in vivo serum stability, pharmacokinetics, and in vivo serum half-life, has been demonstrated. Extensive engineering of the Fc domain of aglycosylated antibodies enables recruitment of various effector functions, despite the lack of N-linked glycans. This review summarizes recent research, preclinical advancements, and clinical development of E. coli-produced aglycosylated therapeutic antibodies as monoclonal, bispecific, and antibody-drug conjugates for use in autoimmune, oncology, and immuno-oncology areas.Abbreviations: ADA Anti-drug antibody; ADCC Antibody-dependent cellular cytotoxicity; ADCP Antibody-dependent cellular phagocytosis; ADC Antibody-drug conjugate; aFc Aglycosylated Fc; AMD Age-related macular degeneration aTTP Acquired thrombotic thrombocytopenic purpura; BCMA B-cell maturation antigen; BLA Biologics license application; BsAb Bispecific antibody; C1q Complement protein C1q; CDC Complement-dependent cytotoxicity; CDCC Complement-dependent cellular cytotoxicity; CDCP Complement-dependent cellular phagocytosis; CEX Cation exchange chromatography; CFPS Cell-free protein expression; CHO Chinese Hamster Ovary; CH1-3 Constant heavy chain 1-3; CL Constant light chain; DLBCL Diffuse large B-cell lymphoma; DAR Drug antibody ratio; DC Dendritic cell; dsFv Disulfide-stabilized Fv; EU European Union; EGFR Epidermal growth factor receptor; E. coli Escherichia coli; EpCAM Epithelial cell adhesion molecule; Fab Fragment antigen binding; FACS Fluorescence activated cell sorting; Fc Fragment crystallizable; FcRn Neonatal Fc receptor; FcɣRs Fc gamma receptors; FDA Food and Drug Administration; FL-IgG Full-length immunoglobulin; Fv Fragment variable; FolRαa Folate receptor alpha; gFc Glycosylated Fc; GM-CSF Granulocyte macrophage-colony stimulating factor; GPx7 Human peroxidase 7; HCL Hairy cell leukemia; HIV Human immunodeficiency virusl; HER2 Human epidermal growth factor receptor 2; HGF Hepatocyte growth factor; HIC Hydrophobic interaction chromatography; HLA Human leukocyte antigen; IBs Inclusion bodies; IgG1-4 Immunoglobulin 1-4; IP Intraperitoneal; ITC Isothermal titration calorimetry; ITP Immune thrombocytopenia; IV Intravenous; kDa Kilodalton; KiH Knob-into-Hole; mAb Monoclonal antibody; MAC Membrane-attack complex; mCRC Metastatic colorectal cancer; MM Multipl myeloma; MOA Mechanism of action; MS Mass spectrometry; MUC1 Mucin 1; MG Myasthenia gravis; NB Nanobody; NK Natural killer; nsAA Nonstandard amino acid; NSCLC Non-small cell lung cancer; P. aeruginosa Pseudomonas aeruginosa; PD-1 Programmed cell death 1; PD-L1 Programmed cell death-ligand 1; PDI Protein disulfide isomerase; PECS Periplasmic expression cytometric screening; PK Pharmacokinetics; P. pastoris Pichia pastoris; PTM Post-translational modification; Rg Radius of gyration; RA Rheumatoid arthritis; RT-PCR Reverse transcription polymerase chain reaction; SAXS Small angle X-ray scattering; scF Single chain Fv; SCLC Small cell lung cancer; SDS-PAGE Sodium dodecyl sulfate-polyacrylamide gel electrophoresis; SEC Size exclusion chromatography; SEED Strand-exchange engineered domain; sRNA Small regulatory RNA; SRP Signal recognition particle; T1/2 Half-life; Tagg Aggregation temperature; TCR T cell receptor; TDB T cell-dependent bispecific; TF Tissue factor; TIR Translation initiation region; Tm Melting temperature; TNBC Triple-negative breast cancer; TNF Tumor necrosis factor; TPO Thrombopoietin; VEGF Vascular endothelial growth factor; vH Variable heavy chain; vL Variable light chain; vWF von Willebrand factor; WT Wild type